Relaciones maritales, relaciones paternas y su influencia en el ajuste psicológico de los hijos (2006)
The purpose of this research was to inquire to what extend the functioning characteristics of couples both in their role as partners and parents contribute to the psychological adjustment of their children. The study aimed to establish if the exercise of certain rearing practices contributes to the development of adjustment behaviors. This research was carried out with a sample of 256 families constituted by both parents and a child between the ages of 12 and 18 years old. Results reveal that certain characteristics of couples functioning such as marital satisfaction, parental satisfaction, marital conflict and parental stress, are important to explain the variability of psychologically adjusted behaviors in their children. Likewise, the type of support given to children, the monitoring of their activities, the psychological control and the harsh parenting, do contribute to the development of either adjustment behaviors or psychological imbalance.